Ground detection of terrestrial gamma ray flashes from distant radio signals. Issue 16 (19th August 2016) - Lyu, Fanchao; Cummer, Steven A.; Briggs, Michael; Marisaldi, Martino; Blakeslee, Richard J.; Bruning, Eric; Wilson, Jennifer G.; Rison, William; Krehbiel, Paul; Lu, Gaopeng; Cramer, Eric; Fitzpatrick, Gerard; et al.
Abstract: Terrestrial gamma ray flashes (TGFs) are brief bursts of energetic gammy‐ray photons generated during thunderstorms, which have been detected almost exclusively by satellite‐based instruments. Here we present three lines of evidence which includes the three out of three simultaneously observed pairs, the same occurrence contexts, and the consistent estimated occurrence rate, which indicate a direct relationship between a subset of TGFs and a class of energetic radio signal easily detectable by ground‐based sensors. This connection indicates that these gamma ray and radio emissions are two views of the same phenomenon and further enable detection of these TGFs from ground distant radio signals alone. Besides dramatically increasing the detection rate of TGFs, this ground detection approach can identify TGFs in continental and coastal areas that are at latitudes too high for present TGF‐detecting satellites and will provide more insights into the mechanism of TGF production. Key Points: +EIPs and a subset of TGFs are intrinsically linked, and they are the two views of the same phenomenon +EIPs can serve as a proxy for the ground detection of TGFs from distant electromagnetic radio signals More measurements can be done on +EIP‐TGFs on land and thus deepen the insight into TGFs